PP21 Non-technical skills in the out-of-hospital cardiac arrest – identification for future practice. Issue 10 (24th September 2019) - Cormack, Stef; Scott, Steve; Stedmon, Alex
Abstract : Background: The use and assessment of non-technical skills (NTS) in healthcare has gained recognition in recent years. Mainly adopted from aviation key NTS have enabled specific teams such as surgical and anaesthetics, to improve leadership, communication and situational awareness. Paramedic NTS have been identified but in the out-of-hospital cardiac arrest (OHCA) there is limited evidence. This study aims to identify NTS in the OHCA to inform the design of an assessment tool to improve overall management of an OHCA. Methods: A review of the literature including NTS in the OHCA and existing behavioural marker tools was completed using online databases (Medline, PubMed, AMED, PsycINFO, PsycARTICLES and CINAHL) and MeSH terms (out-of-hospital, prehospital, paramedic, ambulance, EMS, non-technical skills, soft skills, human factors and behavioural marker systems). Key NTS were taken from the literature and explored by three focus groups (numbers 5, 6, 6). Focus groups comments were transcribed and thematic analysis used to identify noteworthy NTS that could be used to design a tool for assessing NTS in a simulated OHCA. Participants were also asked to rank the most important NTS relevant to an OHCA. Results: The literature review revealed limited evidence for NTS in the OHCA but identified existing behavioural marker systems in healthcare, although not for the OHCA. Focus groups explored NTS relevant to the OHCA and ranked in order the most important. Situational awareness, communication, leadership, followership and decision making including knowledge and procedures were identified as the most important NTS relevant to an OHCA. Conclusions: There is no existing assessment or behavioural marker tool for assessing NTS in the OHCA. Focus groups identified key NTS relevant to the OHCA which could be used to design an assessment/behavioural marker tool to assess individuals in a simulated OHCA.